Modeling Erosion in Hollow Cylinder Tests: The Case of Low Pressure Under Variable Confining Stress - Kakonitis, Panayiotis; Papaloizou, Loizos; Gravanis, Elias; Sarris, Ernestos (My University, 2024)
Modelling the erosional behavior of rock cores in hollow cylinder tests is a formidable task because it involves coupled hydro-mechanical processes. In a recent work of the authors, we proposed semi-analytical hydro-mechanical framework for modelling erosion at laboratory scale through the hollow cylinder test. The model was based on the kinematic formulation of classic hydro-mechanical models also known as volumetric sand production models. The original formulation was constructed to include variable confining stress and flow rate conditions. In this new formulation, a power law dependency of the erosion coefficient λ with stress is incorporated to investigate its dependency on the variable external radial stress boundary condition reflected on the sand production curve. This is a significant update with respect to the previous formulation that assumed a constant sand production coefficient. Results show an improved performance with respect to experimental results. This model can be used to systematically calibrate sand production coefficients for different types of rocks.
Keywords: Geology; Wellbore design; Flow assurance; Reservoir characterization; Sand control; Geomechanics; Reservoir surveillance